Application of Law Based on the Principle of Lex Spesialis Derogat Legi Lex Generalis in the Crime of Online Gambling (Decision Number 232/PID.B/2022/PN.CBD) - Mela Meiliawati (Yayasan Adra Karima Hubbi, 2023)
Background. The existence of internet technology can make it easier for people to get information and facilitate communication, but the internet can also have a negative impact on society, one of which is a medium for finding information or sites that contain gambling. This can change the pattern of ordinary or conventional gambling to gambling with internet media or what is commonly called online gambling, so that it can be accessed anytime and by anyone. Purpose. Gambling is a prohibited act as stipulated in Article 303 of the Criminal Code, 303 bis of the Criminal Code, and Article 27 paragraph (2) of the Law on information and electronic transactions. In verdict number 233/Pid.B/2022/Pn.Cbd the author found a discrepancy in the application of the article, so the problem in this study is